Factors Affecting Tax Avoidance at Food and Beverage Companies - Sanjaya, Caroline Christie; Yuniarwati, Yuniarwati (Syntax Corporation, 2024)
The purpose of this research to examine the factors that influencing Tax Avoidance. Those factors are Profitability, Leverage and Sales Growth to Tax Avoidance. The population of this research consists of food and beverage subsector manufacturing companies listed in Indonesia Stock Exchange from 2020 to 2022. Samples are obtained through purposive sampling method, in which only 33 food and beverage companies meet all sampling criteria resulting 92 data available are taken as the samples. This research used multiple regression method to test the effect of each variable in influencing tax avoidance. The research data was analyzed using SmartPLS Version 3 software. The result of this research indicates that profitability have influence to tax avoidance, while leverage and sales growth have no influence to tax avoidance.